PELATIHAN PENENTUAN ARAH KIBLAT BAGI SANTRI PONDOK PESANTREN HIDAYATUL QUR’AN (PPHQ) - Moelki Fahmi Ardliansyah; Sakirman Sakirman; Jamil Jamil (DEVOSI, 2023)
Astronomy in Indonesia originates and develops from Islamic boarding schools. Currently, this science is not massively studied in Islamic boarding schools, because it is considered difficult to do something related to calculations. Whereas in the aspect of study in Fiqh, students are taught and given an in-depth explanation. The Hidayatul Quran Islamic Boarding School (PPHQ) in Batanghari, East Lampung, is no exception, which has two flagship programs, namely Diniyah Takmiliyah and Tahfidhul Qur'an. In the Diniyah Takmiliyah Program, where alfiyah class students have studied fiqh studies quite in depth, the study of istiqbalul qiblah fiqh is not overlooked. This service tries to complete the fiqh understanding of the Qibla that has been owned by the santri with a scientific understanding of the Qibla, both in terms of calculation and measurement. The method used is PAR (participatory action research) with the aim of seeing, hearing, as well as understanding social phenomena that occur. Through this method, the target community or group is used as a subject, not an object of activity. The results obtained were that the alfiyah class students had basic knowledge both in the field of fiqh and about the geography of the earth. So that this training can complement and add insight, knowledge, new understanding and new skills in determining the Qibla direction.